Innovative method with two-stage surgery for Ewing sarcoma with personalized distal clavicle reconstruction: A case report and diagnosis review - Arunwatthanangkul, Patcharapol; Piyabenjarad, Panichanok; Wisitthipakdeekul, Siraprapa; Chobpenthai, Thanapon (Frontiers in Oncology, 2023)
A 13-year-old boy presented with a growing lump at left clavicle for 5 months. Plain radiograph revealed an osteolytic mass with aggressive periosteal reaction, suggesting a malignant lesion. Advanced imaging and histopathological examinations revealed that the patient had Ewing sarcoma without metastasis. The two-stage surgery: Resection-Observation-Reconstruction. Underlying rationale was that Ewing sarcoma has high recurrence. After 2 years of resection, patient had remission, and he currently has a personal 3D-printed titanium implant with intact shoulder function.